Determinan Tingkat Pengangguran Terbuka Kabupaten/Kota di Provinsi Bali - widi suryawan ratha (Jurnal Ekonomi Pembangunan, 2018)
This study was conducted with a background of unemployment rate in Bali that fluctuate and unemployment rate is very important used to measure the success rate in economic development in a region. The high unemployment rate in a region indicates low economic growth in the region. Labor force, labor force participation rate, average length of school, population, and district minimum wage becomes one of the determinants of the unemployment rate in addition to the population. An increase in the unemployment rate is also affected by the minimum wage. Therefore, this study would like to analyze the linkage of labor force, labor force participation rate, gross regional domestic product, average length of school, population, district minimum wage to open unemployment in Bali Province to achieve inclusive growth in Bali short term and long term. The result is labor force have a positive and significant effect to open unemployment, the labor force participation rate, the population size and the district minimum wage have a negative and significant effect to open unemployment. The labor force participation rate has the greatest effect compared to other variables. The model specification is justified and gives an indication of the short- and long-term relationships of the observed variables.